CREDIT–MODULE SYSTEM IN HIGHER EDUCATION INSTITUTIONS (EUROPEAN SYSTEM) - Ergashev Muhammadsodiq Uchqun o‘g‘li (Journals Park Publishing, 2026)
The article highlights the key principles of the credit–module system (ECTS) formed within the European Higher Education Area (EHEA), the distribution of credits within the three-cycle (bachelor–master–doctorate) structure, and a comparison of the application of the 180 and 240 ECTS models at the bachelor level based on real statistical data from the 2010/11 academic year. It also analyzes the stages of introducing the credit–module system in Uzbekistan’s higher education system on the basis of the concept and government decisions adopted for the period up to 2030, as well as target indicators (including the task of transferring 85% of higher education institutions to the credit–module system by 2030). Based on secondary data analysis and a review of regulatory and legal documents, the paper discusses adapting the European ECTS model to Uzbekistan’s conditions, increasing the share of students’ independent work, changes in teachers’ assessment practices, and integration of the educational process with management information systems. The Results section presents a real statistical table and a bar chart reflecting the distribution of 180- and 240-credit programmes across EHEA countries. The Discussion section considers, along with the advantages of the credit–module system, issues such as ensuring workload–credit balance, digital competencies, and the reliability of assessment, and provides practical recommendations for higher education institutions of Uzbekistan.
Keywords: Credit–module system, ECTS, European Higher Education Area (EHEA), three-cycle system, bachelor, master, Uzbekistan, education reforms.